2021
DOI: 10.1093/omcr/omab052
|View full text |Cite
|
Sign up to set email alerts
|

Orchiepididymitis in the context of multisystem inflammatory syndrome in a child with Covid-19 from Syria: a very rare presentation for SARS-Cov-19 in children

Abstract: The coronavirus disease 2019 (COVID-19) is still striking the global population affecting all age groups. So far, many clinical features associated with COVID-19 illness remain under-identified, especially atypical manifestations. It is essential to characterize associated rare symptoms to better recognize complications. As severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causes Multisystem Inflammatory Syndrome in children (MIS-C) in severe infection manifesting as a generalized inflammatory react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Both had unilateral inguinal swelling and erythema. 4,5 Another reported scrotal ulcers as a presentation of MIS-C. 6 Yet, these presentation remains rare for MIS-C, which indicates the need to remain vigilant when dealing with its differing presentations. To the best of our knowledge, this is the first reported case of scrotal pain as a symptom of MIS-C in Riyadh, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both had unilateral inguinal swelling and erythema. 4,5 Another reported scrotal ulcers as a presentation of MIS-C. 6 Yet, these presentation remains rare for MIS-C, which indicates the need to remain vigilant when dealing with its differing presentations. To the best of our knowledge, this is the first reported case of scrotal pain as a symptom of MIS-C in Riyadh, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the plethora of cells with ACE2 expression in the genitourinary tract, testicular cells might be a target for the disease. 5 Nonetheless, no clear mechanism is established yet.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of orchiepididymitis associated with COVID-19 was reported in a 14-year-old boy in Italy (7). After that, M.Haydar et al reported a case of epididymitis in the setting of MIS-C (multisystem inflammatory syndrome in children) in a 7-year-old boy from Syria (8). In a systematic review conducted on 575 patients, including 538 males, scrotal discomfort, swelling, pain, and erythema were described in 39 patients, among whom acute orchitis was found in 10 patients and acute orchiepididymitis in 10(3).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the urogenital Case Reports in Urology complications caused by COVID-19 have been secondary to hypercoagulable states [5]. There are some case reports regarding patients with epididymo-orchitis symptoms such as abdominal, testicular, and back pain; bilateral testicular warmth, testicular discomfort, swelling, pain, and erythema; and concurrent COVID-19, without any respiratory symptom [5,6,[10][11][12][13]. These studies reported NSAID or antibiotic therapy would be successful in all patients with testicular pain, and no patient required more invasive procedures [4,6,14,15].…”
Section: Discussionmentioning
confidence: 99%